Pengembangan Ekonomi Daerah melalui Sektor Unggulan Kota Surabaya dalam Masa Pandemi Covid-19 - Yusuf Hariyoko; Anggraeny Puspaningtyas; Eureka Ratna Nirmala; Nabilla Larasati (JPSI (Journal of Public Sector Innovations), 2022)
The purpose of this study is to describe regional economic development through leading sectors in the city of Surabaya during the Covid-19 pandemic. During the Covid-19 pandemic, the regional economy received quite severe impacts, including reduced working hours, decreased wages, and a more serious problem was increasing unemployment and the inability to absorb new workers. The research uses a qualitative descriptive method with a research focus on four main components of regional economic development, namely the development of the economic base, institutions, human resource development, and technology development – technology adaptation. Data collection techniques were carried out by interview and document study. Sources of data come from Bappeda, the City Cooperatives and Micro Enterprises Service and the Surabaya City Manpower Service. The results of the study show that locality development by the Surabaya City government in the midst of the COVID-19 pandemic is carried out both physically in the form of facilities and infrastructure and non-physical development by conducting training needed by the community. In general, the institutional aspects are adequate, but their participation is still not as desired. In the aspect of human resource development, the development program is carried out by providing briefings to the community both related to honing skills or briefing on the rights they should get as workers. Aspects of technology adaptation are carried out through the development of the Ecobis System such as the MSME product marketplace. However, improvements also need to be made to overcome some of the weaknesses in each of these components.